Seasonal migration and improving living standards in Vietnam - de Brauw, Alan; Harigaya, Tomoko (Wiley, 2007)
We use panel data methods to explore whether households in Vietnam used seasonal migration to increase their living standards during the 1990s. Using per capita expenditures as our primary measure of living standards and historical and latent network variables as instruments for migration, we can attribute 5.2 percentage points of annualized expenditure growth to increased migration. The results are robust to several alternative measures of living standards. As the estimates suggest migration accounts for a 3 percentage point decrease in the poverty headcount, we conclude migration played an important role in the improvement of living standards observed in Vietnam.